The Cambridge companion to twentieth-century literature and politics - Hadjiyiannis, Christos; Potter, Rachel (Cambridge companions to literature, 2023)
For a long time, people had been schooled to think of modern literature's relationship to politics as indirect or obscure, and often to find the politics of literature deep within its unconsciously ideological structures and forms. But twentieth-century writers were directly involved in political parties and causes, and many viewed their writing as part of their activism. This Companion tell a story of the rich and diverse ways in which literature and politics over the twentieth century coincided, overlapped - and also clashed. Covering some of the century's most influential political ideas, moments, and movements, nineteen academic experts uncover new ways of thinking about the relationship between literature and politics. Liberalism, communism, fascism, suffragism, pacifism, federalism, different nationalisms, civil rights, women's rights, sexual rights, Indigenous rights, environmentalism, neoliberalism: twentieth-century authors wrote in direct response to political movements, ideas, events, and campaigns.